Communities that care: building community engagement and capacity to prevent youth behavior problems - Fagan, Abigail A. (Oxford University Press, 2019)
Overview of the communities that care system : theoretical basis, development, evaluation, and comparison to other community-based preventive interventions -- Community-based prevention of youth behavioral health problems -- Theoretical perspectives guiding the development and evaluation of CTC -- The development and evaluation of CTC -- Implementing CTC and similar community-based preventive interventions -- The importance of readiness and high-functioning coalitions in community-based prevention -- Improving community capacity to conduct comprehensive prevention needs assessments -- Increasing the use of evidence-based interventions to reduce youth behavioral health problems -- Ensuring high quality implementation and sustainability of evidence-based interventions and coalitions -- Evaluating CTC -- Findings from the community youth development study -- A state-wide effectiveness trial of CTC in Pennsylvania -- Moving forward: what is needed to successfully implement CTC and other community-based prevention systems -- The future of CTC and community-based prevention